Pendekatan Komunikasi Persuasif Orang Tua dalam Pembentukan Karakter Terhadap Anak di Desa Susukan Bojonggede - niati, Rachma Nia; Gunawan, Asep; Gustiawati, Syarifah (Komunika: Journal of Communication Science and Islamic Dakwah, 2025)
Character which is a characteristic that is very identical and makes a difference between a person and other humans, character is of course very closely related to a person’s character in living his life. Character and communication do have a fairly strong attachment, but along the way there are not a few communication barriers that become obstacles for the parents themselves during the process of forming a child’s character. Environmental influences cause various social symptoms that occur in children in Susukan Bojonggede Village. Through a persuasive communication approach in the formation of children’s character can be pursued by parents in the process of growth and development. This study uses descriptive qualitative research methods, with data collection techniques through observation, interviews and documentation. The data and data sources use primary and secondary data and the validity of the data is through triangulation of sources and triangulation of theory. The reality of persuasive communication that is built between children and parents is due to effective communication through adaptation and a fairly long process, as well as the character building that parents do to children is real because there is a science behind this, including the existence of parenting science which become one of the main foundations for parents in Susukan Bojonggede Village in forming noble character, with interactive communication discipline that builds persuasive communication can be transferred in accordance with their hopes and goals, each parent uses their own way to guide their child. However, in the process of forming children, similar methods are carried out, including maximizing time, and prioritizing children in daily routines by communicating, conducting educational visits, through eating together and indirectly each of them of course instills good values to shape the child’s character.